Az orosz geopolitikai gondolkodás áttekintés - Szilágyi István (Geopolitikai szemle, 2019)
The Russian Geopolitics ‒ likewise the western-type of geopolitical schools ‒ has been formed as a consequence of scientific analyses of the role of geographical, historical and spatial elements in the life of society. Its charasteristic features and topics are determined by the changes in the historic conditions of existence, the aspects of civilization, the attitude towards the neighbouring and/or conquering states and empires, the constant seeking of identity, that is the historical process which originates from the position of Rus aiming at creating powerful empire. In the progress of Russian geopolitical way of thinking the space and its role have especially been emphasized on. With in these topics the scientists have been laying stress on seeking its own way, the problems of relationship to Europe and the formation of empire. In the light of responses to the questions several streams – such as „Occidentalists” (oriented-to-the-west), Slavophile stream, Eurasianism and NeoEurasianism have been distinguished. After the cessation of the Soviet Union the Russian political „mainstream” has paid special attention to the Russian Geopolitics. It especially makes use of Alexander Dugin’s views. He is the representative of the so-called „Moscow School” becoming known from the 1990s. Alexander Dugin deals with the Eurasian features of Russia, the four-poled system of the world, repatriating the spheres of influence, the Atlanticism led by the USA and ideas against the one-poled globalization.